Estimation of Adult Mortality in Nigeria in the Era of Sustainable Development Goals: Insights from Census-Based Methods - Okoro, Chinonso Onyinyechi; Nwogu, Eleazar Chukwunenye (Journal of Population and Social Studies [JPSS], 2019)
This paper focuses on the estimation of adult mortality in Nigeria. The general objective is to obtain adult mortality levels for Nigeria which may be relevant in assessing the level of development and the progress of Sustainable Development Goals (SDGs) in that country. Census-based methods were applied to the 1991 and 2006 adjusted population census by age and sex to estimate adult mortality. The results of the study suggest that adult males in Nigeria have a higher life expectancy than their female counterparts in almost all age groups. At age 5-9, the life expectancy from the methods applied was below 60 years. The consequences of low life expectancy among adults include the early marriage of young girls, an increasing orphanhood burden, and high numbers of out-of-school children, which may hamper the achievement of SDGs in the country. Given that there is no consensus yet on the best approach for estimating adult mortality in developing countries, we recommend that census-based methods should be used for this task.